The availability of essential medicines for diabetes at health facilities in Bangladesh: evidence from 2014 and 2017 national surveys - Shariful Hakim; Muhammad Abdul Baker Chowdhury; Nasar U. Ahmed; Md Jamal Uddin (BMC, 2022)
Abstract Background Bangladesh ranks among the world's top ten countries in the number of diabetic patients. The prevention of this disease requires treating patients with essential medicines, and the first crucial step in the uptake of these medicines is availability. We aimed to assess the availability of essential medicines for diabetes (EM-Diabetes) and to explore health facility characteristics associated with the availability of those medicines. Methods We performed the analysis using nationally representative data from the two waves of the cross-sectional Bangladesh Health Facility Survey (BHFS) in 2014 and 2017. Data are available for 1548 and 1524 health facilities in the 2014 and 2017 BHFS. Study samples of this study were 217 facilities (73 from 2014 and 144 from 2017) that offer diabetes diagnosis and treatment services. The outcome variable 'EM-Diabetes availability' was calculated as a counting score of the tracer medicines: metformin, glibenclamide, injectable insulin, and injectable glucose solution. A multivariable Poisson regression model was used to identify the health facility characteristics (such as, managing authority, location, external supervision, regular quality assurance activities, national guidelines for diagnosis and management of diabetes, etc.) associated with EM-Diabetes availability. Results Since 2014, there have been minimal increases in Bangladeshi health facilities that provide diabetes screening and treatment services (from 4.7% to 9.4%). Among facilities offering diabetes services, 64.5% (BHFS 2014) and 55.7% (BHFS 2017) facilities had no EM-Diabetes on-site at all. Between 2014 and 2017, the availability of metformin increased (from 27.5% to 40.1%), but there was a decrease in the availability of glibenclamide (from 16.5% to 9.1%), injectable insulin (from 20.4% to 11.4%), and injectable glucose solution (from 20.4% to 19.2%). Furthermore, publicly owned facilities [relative risk (RR) = 0.44, 95% confidence interval (CI): 0.25-0.78 for 2014 and RR= 0.54, 95% CI: 0.41-0.71 for 2017] and facilities in rural settings [RR= 0.26, 95% CI: 0.12-0.55 for 2014 and RR= 0.60, 95% CI: 0.44-0.81 for 2017] were significantly associated with decreased availability of EM-Diabetes in both survey years. Moreover, routine user fees [RR=3.70, 95% CI: 1.86-7.38] and regular quality assurance activities [RR= 1.62, 95% CI: 1.12-2.34] were also significantly associated with increased EM-Diabetes availability in 2017 only. Conclusions Overall, the health facilities in Bangladesh had insufficient essential medicines for treating diabetes. In general, the availability of EM-Diabetes declined from 2014 to 2017, except for metformin. Policymakers should consider a wide range of policy implications, focusing on the management of public facilities, rural facilities, routine user fees, and quality assurance activities to improve the availability of EM-Diabetes at health facilities in Bangladesh.